Metamorphic evolution of the Loma Marcelo skarn within the geotectonic context of the crystalline basement of the Ventania System (Argentina) - Ballivián Justiniano, Carlos A. (2019)
This study describes the mineralogical and isotopic changes that carbonate xenoliths experienced under multiple metamorphic events and hydrothermal fluid circulation during the evolution of the Ventania System basement. The high reactivity of carbonate xenoliths allowed the preservation of mineral assemblages corresponding to at least three metamorphic events in the resulting Loma Marcelo skarn. The Ventania System basement is composed of Neoproterozoic granites and ignimbrites, Early Cambrian granites, and Middle Cambrian rhyolites. Carbonate xenoliths were incorporated during the intrusion of a calc-alkaline granite with an LA-ICP-MS U-Pb crystallization age of 621.6 ± 2.2 Ma. The intrusion induced pyroxene–hornfels facies metamorphism in the carbonate xenoliths and the associated metasomatism generated calcic and magnesian skarns depending on the protolith composition. Garnet, clinopyroxene, wollastonite, bytownite, and meionite were formed in the calcic skarn (CaS), whereas forsterite and spinel were formed in the magnesian skarn (MgS). Crystallization of Early Cambrian alkaline granites was accompanied by intense hydrothermal activity that was responsible for low temperature (≤300 °C) F-metasomatism in the skarn, as evidenced by the presence of F-rich vesuvianite (CaS) and chondrodite (MgS), among other minerals. Vesuvianite was formed from calc-silicate mineral assemblages of the previous metamorphic event, whereas chondrodite was formed by replacement of forsterite. The low temperature formation of these typical high-grade minerals could be an evidence of mineral formation under disequilibrium conditions favoured by the high reactivity of hydrothermal fluids. Neopalaeozoic basement mylonitization under greenschist facies metamorphism was accompanied by hydrothermal fluid circulation. This event promoted extreme mobility of chemical elements in the basement rocks and epidotization (CaS) and serpentinization (MgS) in the Loma Marcelo skarn. The elongated and boudinaged shape of the skarn bodies, parallel to the mylonitic foliation, is a consequence of dextral shearing that affected the basement rocks. Additionally, almost pure grossular crystallized post-tectonically in the CaS. Carbonates of the Loma Marcelo skarn are depleted in 13C and 18O (δ13CV-PDB = −2.5/−10.1‰; δ18OV-SMOW = +7.3/+14.0‰) relative to carbonate sedimentary rocks. The δ13C and δ18O variations can be attributed to the interaction between large amounts of hydrothermal fluids (W/R = 30–50) and Neoproterozoic carbonate sedimentary rocks.